Structural validity and reliability of the "Oral Health Assessment Tool" applied by speech-language therapists in a population of older Chilean people - Camilo Morales; Felipe Henríquez; Sergio Muñoz (BMC, 2023)
Abstract Background A good state of oral health allows people to communicate and eat. This topic is relevant in older people given its close relationship with their general health. At present, health challenges are directed at detecting and preventing oral disorders and are seen to exclusively by dentists, because the existing instruments can only be applied by them. However, speech-language therapists undergo similar training, which would allow them to collaborate in these processes. In this context, the Oral Health Assessment Tool (OHAT) is a detection instrument with good psychometric properties that is currently available for non-dental use. The objective of this study is the translation into Chilean Spanish of the OHAT and a structural validation of that version for application by these professionals. Materials and methods A mixed qualitative-quantitative study was carried out. The OHAT instrument was adapted to Chilean Spanish and subsequently subject to structural validity and evaluation of internal consistency reliability, as well as a valuation of its reproducibility in 286 older people (166 female, 120 male) from different health contexts. Results The cultural adaptation of the instrument proved to be semantically consistent with the original instrument. Its application was considered to be speedy and simple in the pre-test. The confirmatory factor analysis evidenced the unidimensionality of the OHAT. In addition, the instrument shows good internal consistency and test-retest reliability. Conclusions The OHAT instrument was considered to possess adequate structural validity and test-retest reliability properties. Its usefulness in the context of oral health disorders of this population in Chile is discussed.